Genesis and Significance of the Systemic Approach: Philosophical and Legal Bases - Haykyants, A.; Gyanjumyan , Y. (Bulletin of Yerevan University C: Jurisprudence, 2016)
Systemic approach as one of the main methods of scientific research becomes more actual in conditions of the current complications and differentiation of the legal regulation levels of social relations. This article explores the prerequisites of the origin and philosophical and legal bases of the systemic approach, as well as new horizons for the application of this method in the legal phenomena studies.
Keywords: Genesis and Significance of the Systemic Approach: Philosophical and Legal Bases